E-Training Application for Technical Maintenance Department of Motorcycle Workshop - Mohammed, Abdulwahab Ali (2009)
The main objectives of this study are to design a web-based e-training application for maintenance of the workshop. The prototype which is developed by JSP for workshop is tested and evaluated by using usability test and in order to get know the percentage of the acceptability of the system. The application of the Web-based technologies in this study enables trainer and trainee to teach and learn through online Trainer.